Application of COSMO-RS Method for the Prediction of Liquid-Liquid Equilibrium of Water/n-Dodecane/1-Butanol. (5th February 2014) - Balasubramonian, S.; Kumar, Shekhar; Sivakumar, D.; Mudali, U. Kamachi
Abstract : The liquid-liquid equilibrium (LLE) for the system water-dodecane-butanol was estimated using the UNIQUAC model. In the UNIQUAC model interaction parameters were estimated from the vapor-liquid equilibrium (VLE) and LLE data of their constituent binary pairs. The water-dodecane-butanol LLE was experimentally measured at 298.15 K. Phase stability constraints were taken into account while calculating the binary interaction parameters from the mutual solubility data. The COSMO-RS method was used to estimate the activity coefficient in the miscible binary pair. The ternary LLE composition was predicted using the experimental VLE data as well as using the COSMO-RS calculated activity coefficient data along with the experimental mutual solubility data. In the latter case the root mean square deviation (RMSD) for the distribution of butanol between aqueous and organic phase is 0.24%. The corresponding UNIFAC model prediction is 7.63%.